2022
DOI: 10.1093/braincomms/fcac146
|View full text |Cite
|
Sign up to set email alerts
|

Typical resting-state activity of the brain requires visual input during an early sensitive period

Abstract: Sensory deprivation, following a total loss of one sensory modality e.g. vision, has been demonstrated to result in compensatory plasticity. It is yet not known to which extent neural changes, e.g. higher resting state activity in visual areas (cross-modal plasticity) as a consequence of blindness, reverse, when sight is restored. Here, we used functional MRI to acquire blood oxygen level dependent (BOLD) resting state activity during an eyes open (EO) and an eyes closed (EC) state in congenital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…3 ). These differences are difficult to interpret, though consistent with evidence that the magnitude of activation (often estimated via the amplitude of activity in the low frequency range of the BOLD response) in several brain regions, including precuneus and parietal cortex, varies in adults depending on whether their eyes are open or closed (e.g., Rączy et al, 2022 ). One possibility is that these differences are secondary consequences of previously observed differences in response magnitude in lower-level visual brain regions, including the fusiform gyrus, in these same children ( Bedny et al, 2015 ).…”
Section: Discussionmentioning
confidence: 73%
“…3 ). These differences are difficult to interpret, though consistent with evidence that the magnitude of activation (often estimated via the amplitude of activity in the low frequency range of the BOLD response) in several brain regions, including precuneus and parietal cortex, varies in adults depending on whether their eyes are open or closed (e.g., Rączy et al, 2022 ). One possibility is that these differences are secondary consequences of previously observed differences in response magnitude in lower-level visual brain regions, including the fusiform gyrus, in these same children ( Bedny et al, 2015 ).…”
Section: Discussionmentioning
confidence: 73%
“…Further, neuronal spiking was increased in dark reared mice when exposed to ambient light (Benevento et al, 1992). Crucially, increased visual cortex thickness (Feng et al, 2021; Guerreiro et al, 2015; Hölig et al, 2023) and higher BOLD activity during rest with the eyes open (Raczy et al, 2022) have been observed for CC individuals as well, suggesting incomplete recovery of cortical structure and function after sight restoration in humans. Thus, the restored feedforward drive to visual cortex after surgery might reach a visual cortex with a lower threshold for excitation, possible due to a relatively higher number of excitatory synapses (Bourgeois, 1996; Morales et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These visual deficits in congenital cataract-reversal individuals have been attributed to altered neural development due to the absence of vision, as individuals who suffered from developmental cataracts do not typically display a comparable severity of impairments (Lewis & Maurer, 2009; Sourav et al, 2020). While extant literature reported correlations between structural changes and behavioral outcomes in congenital cataract-reversal individuals (Feng et al, 2021; Guerreiro et al, 2015; Hölig et al, 2023; Pedersini et al, 2023), functional brain imaging (Heitmann et al, 2023; Raczy et al, 2022) and electrophysiological research (Bottari et al, 2016; Ossandón et al, 2023; Pant et al, 2023; Pitchaimuthu et al, 2021) have started to unravel the neural mechanisms which rely on visual experience during sensitive periods for development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation